Tetangga online: Online communities and the role of urban women in the digital sphere - Sihanani, Dyah Esti; Sinaga, Agustinus Alexander (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2026)
The growth of internet-based home décor communities has introduced new forms of digitally mediated social interaction within contemporary urban society. In Indonesia, studies on women-centered online communities have predominantly focused on fandom or religious groups, leaving domesticity-based digital communities relatively underexplored. This study is aimed at examining the meaning of the term “tetangga online” and to analyze how domesticity, online visibility, and identity negotiation are constructed among urban women in digital environments. Employing a qualitative design with a digital ethnography approach, this research focuses on the Home Decor Tour Indonesia (HDTI) community on Instagram. Data were collected through in-depth interviews with six participants and observations of interaction patterns in captions and comment sections, including the analysis of 68 featured homeowners’ posts. The findings reveal that “tetangga online” represents a culturally embedded form of digital neighbourliness that recontextualizes traditional neighborhood interactions into the online sphere. Furthermore, the online display of domestic spaces through home décor practices functions as a strategic medium for women to negotiate their roles within patriarchal social structures while gaining social recognition, solidarity, and potential economic opportunities. This study contributes theoretically by introducing “tetangga online” as an emic concept of digital neighbourliness distinctive to Indonesian urban online communities.